The new rules of marketing & PR : how to use content marketing, podcasting, social media, AI, live video, and newsjacking to reach buyers directly - Scott, David Meerman (N. Jersey Wiley publ., 2020)
"The seventh edition of the pioneering guide to generating attention for your idea or business, packed with new and updated information In the Digital Age, marketing tactics seem to change on a day-to-day basis. As the ways we communicate continue to evolve, keeping pace with the latest trends in social media, the newest online videos, the latest mobile apps, and all the other high-tech influences can seem an almost impossible task. How can you keep your product or service from getting lost in the digital clutter? The seventh edition of The New Rules of Marketing and PR provides everything you need to speak directly to your audience, make a strong personal connection, and generate the best kind of attention for your business. An international bestseller with more than 400,000 copies sold in twenty-nine languages, this revolutionary guide gives you a proven, step-by-step plan for leveraging the power of technology to get your message seen and heard by the right people at the right time. You will learn the latest approaches for highly effective public relations, marketing, and customer communications--all at a fraction of the cost of traditional advertising!"--
Includes index.
Keywords: Internet marketing; Internet in public relations